Perbandingan Aktivitas Daya Hambat Antibakteri Antara Ekstrak Daun Sirih Merah (Piper Crocatum Ruiz & Pav) Dengan Daun Sirih Hutan (Piper Aduncum L) Terhadap Streptococcus Mutans - Abeiasa, M Saka; Humaira, Vilma; Ferdian, Heru (Jurnal Medisains Kesehatan, 2022)
One of the diseases caused by Streptococcus mutans bacteria is dental caries. Dental caries is a condition where there is damage to the tooth-forming tissue structure caused by bacterial activity. The process of dental caries begins with the demineralisation of teeth by the presence of lactic acid and other organic acids that accumulate or accumulate on the surface of the teeth through plaque.This study aims to compare the antibacterial activity of red betel leaf extract (Piper crocatum Ruiz & Pav) and forest betel leaf extract (Piper aduncum L) against Streptococcus mutans bacteria, the cause of dental caries. The research method used was laboratory experiment with statistical analysis using One-Way ANOVA test and Post Hoc LSD test. The results showed that both extracts had antibacterial activity against Streptococcus mutans, with forest betel leaf showing higher activity than red betel leaf. Significant differences were seen at concentrations of 25%, 50%, 75%, and 100%. The forest betel leaf extract had a larger inhibition zone diameter compared to the red betel leaf extract. Nonetheless, both extracts were still less effective than the Amoxicillin control. In conclusion, red betel leaf extract and forest betel leaf extract have potential as antibacterial agents against Streptococcus mutans. However, forest betel leaf extract showed higher activity in inhibiting the growth of these bacteria compared to red betel leaf extract. Therefore, the use of forest betel leaf extract can be an effective alternative in the treatment of dental caries.